Cognitive Burden of Common Non-antiretroviral Medications in HIV-Infected Women. (1st September 2018) - Rubin, Leah H.; Radtke, Kendra K.; Eum, Seenae; Tamraz, Bani; Kumanan, Krithika N.; Springer, Gayle; Maki, Pauline M.; Anastos, Kathryn; Merenstein, Daniel; Karim, Roksana; Weber, Kathleen M.; Gustafson, Deborah; et al.
Abstract : Objective: The aging HIV population has increased comorbidity burden and consequently non-antiretroviral medication utilization. Many non-antiretroviral medications have known neurocognitive-adverse effects ("NC-AE medications"). We assessed the cognitive effects of NC-AE medications in HIV+ and HIV− women. Methods: One thousand five hundred fifty-eight participants (1037 HIV+; mean age 46) from the Women's Interagency HIV Study completed a neuropsychological test battery between 2009 and 2011. The total number of NC-AE medications and subgroups (eg, anticholinergics) were calculated based on self-report. Generalized linear models for non-normal data were used to examine the cognitive burden of medications and factors that exacerbate these effects. Results: HIV+ women reported taking more NC-AE medications vs. HIV− women ( P < 0.05). NC-AE medication use altogether was not associated with cognitive performance. However, among NC-AE medication subgroups, anticholinergic-acting medications, but not opioids or anxiolytics/anticonvulsants, were negatively associated with performance. HIV status moderated the association between these NC-AE medication subgroups and performance ( P 's < 0.05). HIV-serostatus differences (HIV− < HIV+) in global, learning, fluency, and motor function were greatest among women taking >1 anticholinergic medications. HIV-serostatus differences in performance on learning and psychomotor speed were also greatest among women taking 1 or more anxiolytics/anticonvulsants and 1 or more opioids, respectively. Conclusions: HIV+ women have increased cognitive vulnerabilities to anticholinergic, anxiolytic/anticonvulsant, and opioid medications. Potential synergy between these medications and HIV may explain some HIV-related cognitive impairments. It may be important clinically to consider these specific types of medications as a contributor to impaired cognitive performance in HIV+ women and assess the cost/benefit of treatment dosage for underlying conditions. Abstract : Supplemental Digital Content is Available in the Text.